2022
DOI: 10.1371/journal.pone.0270874
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of sexual infection by human papillomavirus and Chlamydia trachomatis in sexually-active women from a large city in the Amazon region of Brazil

Abstract: Background The Human Papillomavirus (HPV) and Chlamydia trachomatis are the most prevalent Sexually Transmitted Infections (STIs) worldwide, and are associated cervical cancer and pelvic inflammatory disease, respectively. However, 80% of women testing positive are asymptomatic. In the Amazon region, young women, in particular, are widely exposed to the infections and their consequences. Objectives Determine the prevalence of sexual infection by HPV and C. trachomatis in young, sexually-active women treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Pregnant women were the target subgroup with the most infection, though their questionnaire response did not collaborate with this finding. Earlier studies had reported higher HPV prevalence among sexually active and pregnant women ( 8 – 10 , 23 ). One common factor among the women subgroups with high infection is being sexually active.…”
Section: Discussionmentioning
confidence: 91%
“…Pregnant women were the target subgroup with the most infection, though their questionnaire response did not collaborate with this finding. Earlier studies had reported higher HPV prevalence among sexually active and pregnant women ( 8 – 10 , 23 ). One common factor among the women subgroups with high infection is being sexually active.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, STI bacteria were detected in 83.0% of symptomatic subjects, a significantly higher percentage than that of asymptomatic subjects (60.1%). 18 In another Brazilian study, the total prevalence of HPV was 15.5%, although the prevalence increased significantly to 32.2% of the women aged less than or equal to 25 years of age. 23.8% of the women that reported having first sexual intercourse at less than 15 years of age, 20% of those that reported having more than one sexual partner over their lifetime but used contraceptives.…”
Section: Discussionmentioning
confidence: 91%
“…with not all HPV genotypes being carcinogenic. 8 The IARC-WHO has classified the genotypes concerning carcinogenicity such that genotypes 6,11 are low-risk HPV, Group 1 hrHPV have genotypes 16,18,31,33,35,39,45,51,52,56,58, and 59 (high-risk carcinogenic), Group 2A with HPV 68 (probably carcinogenic) and group 2B with HPV 26, 30, 34, 53, 66, 67, 69, 70, 73, 82, 85, and 97 (possibly carcinogenic). 1 Considering the high prevalence of HPV worldwide and in India, and the expensive screening strategies, we decided to carry out HPV/STI panel screening in some patients at the Cama and Albless Hospital in Mumbai, Maharashtra for identifying the carcinogenic traits in the patients as a preventive measure against developing cervical cancer.…”
Section: Currently Around 226 Hpv Genotypes Have Been Identifiedmentioning
confidence: 99%
“…In recent studies, the prevalence of HPV remains similar to, or even higher, than the value recorded here (2007)(2008), and the epidemiological profile of women infected with this virus is still very worrying. In 2017, 15.5% of a sample of women in the city of Belém had cervical HPV, and most of them were young, single, with an early onset of sexual life, had several sexual partners in their lifetime, and used oral contraceptives [49]. In this city, a high rate of HPV (63.3%) was also recorded among women with HIV, with a predominance of high-risk HPV genotypes, such as HPV16 (37.5%), and the detection of premalignant alterations in the samples (LSIL (39.4%), HSIL (45.4%), and ASCUS (12.1%)) [27].…”
Section: Discussionmentioning
confidence: 99%